Hydrogen production from glycerol dry reforming over Ag-promoted Ni/Al 2 O 3 - Harun, N. (2019)
In recent times, glycerol has been employed as feedstock for the production of syngas (H 2 and CO) with H 2 as its main constituent. This study centers on dry reforming of glycerol over Ag-promoted Ni/Al 2 O 3 catalysts. Prior to characterization, the catalysts were synthesized using the wet impregnation method. The reforming process was carried out using a fixed bed reactor at reactor operating conditions; 873â1173 K, carbon dioxide to glycerol ratio of 0.5 and gas hourly space velocity (WHSV) in the range of 14.4 â¤ 72 L g cat â1 h â1 ). Ag (3)-Ni/Al 2 O 3 gave highest glycerol conversion and hydrogen yield of 40.7 and 32, respectively. The optimum conditions which gave highest H 2 production, minimized methane production and carbon deposition were reaction temperature of 1073 K and carbon dioxide to glycerol ratio of 1:1. This result can attributed to the small metal crystallite size characteristics possessed by Ag (3)âNi/Al 2 O 3 , which enhanced metal dispersion in the catalyst matrix. Characterization of the spent catalyst revealed the formation of two types of carbon species; encapsulating and filamentous carbon which can be oxidized by O 2 . Â© 2018 Hydrogen Energy Publications LLC